Competencies and Knowledge of Internal Auditor in Islamic Financial Institution : A Literature Review - Gina Nabila; Sulis Rochayatun; Fajar Hafandi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: Recently, the phenomenon of internal audits in Islamic financial institutions is that the fulfillment of sharia principles has not run ideally. This study aims to examine the competence and experience of internal auditors in Islamic financial institutions using a literature review. Method: Data collection techniques were used to search for relevant articles through databases on Emerald, Springer, and Google Scholar by emphasizing keywords related to the theme. Results: The results show that empirical evidence states that the competence and experience of internal auditors in Islamic financial institutions need to be added with several things related to competence and knowledge in accordance with Islamic law, such as knowledge of Islamic principles and laws, especially in fiqh muamalah; a strong understanding of As-Sunnah and Islamic jurisprudence such as ushul fiqh; understanding of accounting and auditing standards that apply within the national territory, as well as standards adopted by other Muslim countries that have implemented sharia auditing and have the competence to argue about the provisions and objectives of sharia. Implications: The implications of this study are expected to be a reference for improving the quality of internal audits in Islamic financial institutions so that they can run in harmony with sharia provisions and principles.Novelty: This study has differences from the studies that have been done before which the difference lies in the object of internal audit in Islamic Financial Institutions and research methods literature review. Therefore, in the next study is expected to conduct research on one of the Islamic financial institutions so that the results obtained can be more specific in accordance with the knowledge and competence of internal auditors at the institution.